MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA PURWABAKTI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Fadilah, Hafid; Syamsiah, Yayah (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This community service aims to design an appropriate sharia microfinance institution model for the people of Purwabakti Village, Pamijahan District, Bogor Regency. The subjects of this community service are the people of Purwabakti Village, Pamijahan District, Bogor Regency, West Java Province. In this community service, activities are carried out based on the method of transparency, participation and accountability. The result of this community service shows that in Purwabakti Villag e there is no formal microfinance institution based on sharia principles. Communities need access to capital that is easy, affordable and in accordance with sharia principles to develop their micro and small businesses. Based on this analysis, a sharia microfinance institution model was designed which includes financing products, savings and other services that refer to sharia principles.